Skill-Based Bimanual Manipulation Planning - Wojciech Szynkiewicz (Journal of Telecommunications and Information Technology, 2012)
The paper focuses on specification and utilization of manipulation skills to facilitate programming of bimanual manipulation tasks. Manipulation skills are actions to reach predefined goals. They constitute an interface between low-level constraint-based task specification and high level symbolic task planning. The task of the robot can be decomposed into subtasks that can be resolved using manipulation skills. Rubik’s cube solving problem is presented as an example of a 3D manipulation task using two-arm robot system with diverse sensors such as vision, force/torque, tactile sensors.